Analisis Perilaku Pengelolaan Sampah Menggunakan Teori Health Belief Model Pada Masyarakat Pesisir - Nurzani; Fifi Nirmala G; Ahmad Saktiansyah , La Ode (Politeknik Baubau, 2025)
Waste refers to any unused, unwanted, or discarded materials resulting from human activities, excluding natural occurrences. According to the World Economic Forum's 2020 data, the world generates approximately 300 million tons of plastic waste annually. Indonesia contributes 187.2 million tons of marine waste yearly. In Sulawesi Tenggara Province, waste generation reached 125,445.34 tons in 2021, increasing to 164,078.87 tons in 2022 and 437,958.44 tons in 2023. Konawe Regency generated 37,785.82 tons in 2021, rising to 38,879.65 tons in 2023. This study investigates the relationship between the Health Belief Model (HBM) and waste management behavior among coastal communities in Bajoe Village, Konawe Regency, in 2024. This quantitative research employs an observational-analytical approach with a cross-sectional design. The population consists of 249 individuals, with 151 samples selected through accidental sampling. Chi-square tests were used for statistical analysis. The result of the study Perceived Susceptibility (P = 0.000), Perceived Barriers (P = 0.000), Cues to Action (P = 0.020), Perceived Severity (P = 0.695), Perceived Benefits (P = 0.818). Based on the research results Perceived Susceptibility, Perceived Barriers, and Cues to Action significantly influence waste management behavior among coastal communities in Bajoe Village, Konawe Regency, in 2024. Conversely, Perceived Severity and Perceived Benefits do not significantly impact waste management behavior.